PENGARUH WORD OF MOUTH, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN KARTU INTERNET IM3 DI PEKANBARU - Dinda, Ulfa Dinda; Nursanti, Aida; Noviasari, Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
One marketing strategy that is quite effective and widely used by entrepreneurs is marketing strategy word of mouth communication. Information gained from others for im3 internet card products becomes a considerable promotion of marketing with improved product quality as well as compatibility between product quality and the price offered. This study aims to determine the effect of word of mouth, product quality and price on purchasing decisions and consumer satisfaction IM3 internet card in Pekanbaru. Respondents of this study amounted to 115 people who use IM3 internet card in Pekanbaru. Data analysis technique used in research is path analysis (Path Analysis) by using SPSS 19. From the test results revealed that the word of mouth significant effect on purchasing decisions, product quality significant effect on purchasing decisions, Price significant effect on purchasing decisions, purchasing decisions have a significant effect on customer satisfaction, Word of mouth significant effect on customer satisfaction through purchasing decisions, Quality product significant influence to consumer satisfaction through purchasing decision, Price have a significant effect to customer satisfaction through purchasing decision. It is expected that the company can adjust the price on each product, because consumers are more concerned with the price on the purchase of the product, considering the price can also attract consumers in buying and improving product quality by providing more bonuses on the internet card so that consumers feel satisfied and returned to buy cards IM3 internet especially on a regular basis..Keywords : Word Of Mouth, Product Quality, Price, Purchase Decision And Consumer Satisfaction